2016
DOI: 10.18632/oncotarget.6840
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin enhances antitumor effect of paclitaxel on cervical tumorigenesis via inhibiting the integrin α2/β5/FAK signaling pathway

Abstract: While Bufalin restrains primary tumorigenesis, the role of Bufalin in cervical cancer remains unclear. Here, we show that Bufalin can inhibit cervical cancer cell proliferation, block cell cycle in G2/M phase, induce cellular apoptosis and reduce cell metastasis through stimulation of p21waf/cip1, p27cip/kip, Bax and E-cadherin, and suppression of cyclin A, cyclin B1, CDK2, Bcl-2, Bcl-xl, MMP9 and SNAIL1. Further study suggests that Bufalin has no apparent damage to human normal cervical cells at the low conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Bufalin is a kind of cardiac glycosides which is derived from the serous fluid secreted by the parotid venom glands and skin of Bufo melanostictus and Bufo bufo gargarizans [20]. Researches have showed that Bufalin has many pharmacological activities, including anti-inflammatory, anti-tumor, antiviral, cardiotonic and narcotic effects [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Bufalin is a kind of cardiac glycosides which is derived from the serous fluid secreted by the parotid venom glands and skin of Bufo melanostictus and Bufo bufo gargarizans [20]. Researches have showed that Bufalin has many pharmacological activities, including anti-inflammatory, anti-tumor, antiviral, cardiotonic and narcotic effects [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…PI3K pathway plays an important role in regulating cell survival, angiogenesis, cell invasion, and metastasis [ 32 ]. Liu et al reported that integrin α2/FAK/AKT1/ GSK3β signaling was involved in cell cycle regulation of bufalin in cervical cancer [ 33 ]. However, the link between PI3K and Aurora kinase has been limitedly described as well as the mechanism by which PI3K regulates mitotic kinase is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Modern research has found BU to have strong anti-tumour effects. Its mechanism involves the inhibition of tumour cell growth and the induction of apoptosis of tumour cells[ 28 , 29 ]. This paper reports, for the first time, an investigation of the function and mechanism of BU in reversing ABCB1-mediated MDR.…”
Section: Discussionmentioning
confidence: 99%